Toward representing wave‐induced sediment suspension over sand ripples in RANS models. Issue 5 (9th May 2013) - Amoudry, Laurent O.; Bell, Paul S.; Thorne, Peter D.; Souza, Alejandro J.
Abstract : [1] Parameterizations of near‐bed sediment processes are commonly associated with the poor predictive skill of coastal sediment transport models. We implement a two‐dimensional Reynolds‐averaged Navier‐Stokes model to directly assess these parameterizations by reproducing measurements obtained in large‐scale wave flume experiments. A sediment transport model has been coupled to wave hydrodynamics and turbulence, and numerical experiments provide temporal and spatial variations of free surface, flow velocity, sediment concentration, and turbulence quantities. Model‐data comparisons enable the direct assessment of how key suspension processes are represented and of the inherent variability of the sediment transport model. We focus on the different processes occurring above rippled beds versus dynamically flat beds. Numerical results show that increasing roughness alone is not sufficient to have good predictive capability above steep ripples. Some parameterization of the vortex entrainment process is necessary and a simple modification, which leads to constant sediment diffusivity above steep‐rippled beds, is sufficient to obtain good predictions of wave‐averaged suspended concentrations. Model‐data comparisons for the turbulent kinetic energy are also presented and highlight the need to account for the effect of vortex entrainment on near‐bed turbulence and transfer of momentum. Key Points: We numerically investigate near‐bed sediment mixing Modified near‐bed diffusivity results in good predictions above steep ripples Turbulence spectral dynamics are modified above steep ripples.